Path Analysis on the Effects of Peer Support and Sanitation Facilities on Personal Hygiene among Female Student having Menstruation in Sragen Central Java - Kunaryanti Kunaryanti; Uki Retno Budihastuti; Yulia Lanti Retno Dewi (Journal of Health Promotion and Behavior, 2019)
Background: Poor personal hygiene during menstruation causes the risk of Reproductive Tract Infection (RTI) in adolescent. It threatens women's health. Personal hygiene is affected by attitude, peer support, and the availability of personal hygiene facilities. This study aims to analyze the determinant of personal hygiene in adolescents during menstruation in Sragen Regency, Central Java.Subjects and Method: This study was an analytic observational study with a cross sectional design. The study was conducted in June 2019. A sample of 200 study subjects was selected for this study by simple random sampling. The dependent variable was personal hygiene. The independent variables were attitude, peer support, and the availability of personal hygiene facilities. The study was collected by questionnaire and analyzed by path analysis.Results: Personal hygiene was directly and positively affected by positive attitude (b=1.38; 95% CI=0.78 to 1.98; p<0.001). Personal hygiene was indirectly affected by strong peer support and the availability of good personal hygiene facility.Conclussion: Personal hygiene is directly and positively affected by positive attitude. Personal hygiene is indirectly affected by strong peer support and the availability of good personal hygiene facility.Keywords: personal hygiene, attitude, peer support, personal hygiene facilitiesCorrespondence:Kunaryanti. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: kunaryanti@yahoo.com. Mobile: +6285700900029.Journal of Health Promotion and Behavior (2019), 4(3): 170-177https://doi.org/10.26911/thejhpb.2019.04.03.02